Impact of Blockchain Technology on Supply Chain Transparency in Japan - Sakamoto, Takesh (American Journal of Supply Chain Management, 2024)
Purpose: The aim of the study was to assess the impact of blockchain technology on supply chain transparency in Japan. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: This study found that blockchain provides a decentralized and immutable ledger that records every transaction in real time, allowing stakeholders to trace the origins of products and monitor their journey through the supply chain. This capability fosters greater accountability and trust among participants, as any alterations to the data can be easily detected. Research indicates that implementing blockchain can reduce fraud and errors, leading to more efficient operations and reduced costs. Furthermore, enhanced visibility into supply chain processes can enable companies to respond more swiftly to disruptions, ensuring better compliance with regulatory standards and improving overall operational resilience. As organizations increasingly adopt blockchain, the technology is expected to revolutionize supply chain management by promoting ethical practices and sustainability, as consumers become more aware of the importance of product sourcing and authenticity. Implications to Theory, Practice and Policy: Transaction cost theory, agency theory and stakeholder theory may be used to anchor future studies on assessing the impact of blockchain technology on supply chain transparency in Japan. Organizations should initiate pilot programs to test blockchain implementations in their supply chains, allowing for real-world assessment of its benefits and challenges. Policymakers should establish clear regulations and standards for blockchain technology in supply chains, ensuring interoperability and data security.